Exploring Cross-Device Web Use on PCs and Mobile Devices - Kane, Shaun K.; Karlson, Amy; Meyers, Brian; Johns, Paul; Jacobs, Andy; Smith, Greg (INTERACT 2009, 2009)
Although many mobile devices allow users to browse the web, mobile users may find it difficult to find and access mobile web sites while on the go. We investigated whether a user’s web browsing activity on another device, such as their PC, could help them find and access web sites on their mobile device. To understand current patterns of cross-device web use, we surveyed 175 smartphone users about their mobile and PC web browsing habits. We found that while users shared web information between devices, they generally used cumbersome manual methods to do so. In a second study, we instrumented 14 participants' PC and mobile phone browsers and tracked the web pages that they visited on each device. We also used experience-sampling surveys to determine whether specific sets of web sites from their PC browsing history would be useful on a mobile device. We found that participants visited many of the same sites on both their mobile device and PC, and that participants were interested in viewing additional sites from their PC on their mobile device. Our results suggest that automatically sharing information about web activities between devices has great potential to improve the usability of the web for mobile devices.